Bioremediation: the eco-friendly solution to the hazardous problem of environmental pollution - Mukherjee, Susmita; Narula, Rajiv; Bhattacharjee, Shreya; Dutta, Debankita; Bose, Indrani; Mahakud, Jitesh; Paul, Sharanya; Bhattacharjee, Sourish; Paul, Sonali (Journal of Environmental Engineering and Landscape Management, 2021)
Bioremediation is a technique to enhance natural biological processes to rectify polluted groundwater, soil, and even entire habitats. Bioremediation techniques use biological agents to act upon hazardous, toxic materials and subsequently convert them into less toxic substances. Microbes are organisms ubiquitously present in the biosphere. These microorganisms are the main agents that remediate toxic and polluted environmental conditions. Highly polluted areas can be rectified using proper bioremediation procedures and interventions. In this review we have studied the different bioremediation techniques which can be utilized to correct the harmful effects of environmental pollution. In this study we have also emphasized on the benefits of adopting bioremediation as an efficient alternative technique in comparison to the traditional physical and chemical methods to restore the healthy environmental conditions.